A Reconsideration of Social Innovation: Drama Pedagogies and Youth Perspectives on Creative and Social Relations in Canadian Schooling - Gallagher, Kathleen (Canadian Journal of Education/Revue canadienne de l'éducation, 2018)
Drawing from a multi-sited, global ethnography on youth civic engagement and artistic practices, the author uses students’ perceptions from one Canadian high school, as they reflect on their experiences in a drama classroom, to ask what we might learn about the macro discourses and processes of social innovation from the local, artistic, and collaborative activities of young people. Learning from young people that they do not imagine themselves as the coherent social grouping our institutions have imagined them to be raises questions about the role educational institutions might be playing in developing and activating plural and progressive forms of sociality and social innovation more broadly.